The effect of working memory maintenance on long-term memory. - Hartshorne, Joshua K.; Makovski, Tal (Memory & Cognition, 2019)
Initially inspired by the Atkinson and Shiffrin model, researchers have spent a half century investigating whether actively maintaining an item in working memory (WM) leads to improved subsequent long-term memory (LTM). Empirical results have been inconsistent, and thus the answer to the question remains unclear. We present evidence from 13 new experiments as well as a meta-analysis of 61 published experiments. Both the new experiments and meta-analysis show clear evidence that increased WM maintenance of a stimulus leads to superior recognition for that stimulus in subsequent LTM tests. This effect appears robust across a variety of experimental design parameters, suggesting that the variability in prior results in the literature is probably due to low power and random chance. The results support theories on which there is a close link between WM and LTM mechanisms, while challenging claims that this relationship is specific to verbal memory and evolved to support language acquisition.